Drosophila melanogaster as a model to study age and sex differences in brain injury and neurodegeneration after mild head trauma - Ye, Changtian; Behnke, Joseph A.; Hardin, Katherine R.; Zheng, James Q. (Frontiers in Neuroscience, 2023)
Repetitive physical insults to the head, including those that elicit mild traumatic brain injury (mTBI), are a known risk factor for a variety of neurodegenerative conditions including Alzheimer's disease (AD), Parkinson’s disease (PD), and chronic traumatic encephalopathy (CTE). Although most individuals who sustain mTBI typically achieve a seemingly full recovery within a few weeks, a subset experience the emergence of delayed-onset symptoms later in life. As most mTBI research has focused on the acute phase of injury, there is an incomplete understanding of mechanisms related to the late-life emergence of neurodegeneration after early exposure to mild head trauma. The recent adoption of Drosophila-based injury models provides several advantages over existing preclinical animal models, including a tractable framework amenable to high-throughput assays and short relative lifespan conducive to lifelong mechanistic investigation. The use of flies also provides an opportunity to investigate important risk factors associated with neurodegenerative conditions, specifically age and sex. In this review, we survey current literature that examine age and sex as contributing factors to trauma-mediated neurodegeneration in humans and preclinical models, including mammalian and Drosophila models. We discuss similarities and disparities between human and fly in aging, sex differences, and pathophysiology. Finally, we highlight Drosophila as an effective tool for investigating mechanisms underlying head trauma-induced neurodegeneration and for identifying therapeutic targets for treatment and recovery.